Adoption of improved amaranth varieties and good agricultural practices in East Africa. (April 2019) - Ochieng, Justus; Schreinemachers, Pepijn; Ogada, Maurice; Dinssa, Fekadu Fufa; Barnos, William; Mndiga, Hassan
Highlights: We quantify adoption of improved amaranth varieties and good agronomic practices for East Africa. Data collected using expert elicitation and a questionnaire survey of seed companies. Improved varieties adopted on 51% of planted area in Kenya and 70% in Tanzania. World Vegetable Center germplasm is found on 46% of planted area and in 59% of seed company sales. Center's amaranth lines reach about 231, 000 farm households in Kenya and Tanzania. Abstract: This study quantifies the adoption of improved amaranth varieties in Kenya and Tanzania, and the extent to which these result from international vegetable breeding research conducted by the World Vegetable Center (WorldVeg) and partners. The study used expert elicitation and a questionnaire survey among vegetable seed producers. Nine expert panels were conducted involving 123 local experts. The results show that improved amaranth varieties were planted on 51% of the planted area in Kenya and 70% in Tanzania. Improved varieties were planted on 17, 502 ha and reached 404 thousand smallholder farmers. WorldVeg is the main source of improved varieties, reaching 231 thousand farm households in Kenya and Tanzania. Seed companies sold 2.9 tons of amaranth seed in 2016 and 59% of this was WorldVeg-based germplasm. Opportunities exist to improve amaranth production through the development and promotion of better varieties (particularly resistance to white rust and leaf spot) and good agronomic practices (particularly the use of certified seed, mineral fertilizers, seed treatment and nurseries). Investment in amaranth research and development will contribute to better livelihoods and better nutrition in sub-Saharan Africa.